China's Silk Road Originates from Nanchong and Develops across the Whole World - Li Houqiang (Contemporary Social Sciences, 2017)
The following views regarding the Southern Silk Road are presented and discussed. First, primitive wild mulberry trees were transplanted from Nanchong to the world. Second, primitive wild silkworms immigrated from Nanchong to the world. Third, the ancient silk of China originated in Nanchong and spread across the world. Fourth, Sichuan silk arrived in Afghanistan and ancient Egypt one thousand years earlier than Zhang Qian’s arrival. Fifth, the appearance of the Southern Silk Road precedes the appearance of the Northern Silk Road and the Maritime Silk Road by hundreds of years. This article supports the belief that as the headstream of the Southern and Northern Silk Road, Nanchong is the intersection of “the Belt and Road”as well as the Yangtze River Economic Belt.